2015
DOI: 10.1111/jfpp.12597
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and Functional Properties of Kariya (Hildergadia barteri) Protein Hydrolysates Obtained with Two Different Proteolytic Enzymes

Abstract: PRACTICAL APPLICATIONSThe study compares the bioactivity of peptides produced from kariya seeds (an underutilized oil seeds) using two different proteolytic enzymes (pepsin and pancreatin). The result showed that kariya seed protein hydrolyzed with pancreatin has better functional properties than those hydrolyzed with pepsin. However, kariya seed protein hydrolyzed with pepsin has better antioxidant properties than those hydrolyzed with pancreatin. Both results compare favorably with that of other oilseeds. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…, & Tananuwong, 2008) while at aqueous phase, greater concentration of soluble protein could enhance foam formulation (Eltayeb et al, 2011). The increase in foaming properties observed at alkaline pH of walnut protein isolate and concentrate (Mao & Hua, 2012) and kariya protein hydrolysates Adiamo, Gbadamosi, and Abiose (2016b) in the report of, agrees to the assertion that foaming properties are pH dependent. The two new varieties of Bambara groundnut samples (BGB and BGW) showed superior foaming capacities over the commercial sample.…”
Section: Effect Of Ph and Nacl Concentration On Emulsifying Activitsupporting
confidence: 83%
“…, & Tananuwong, 2008) while at aqueous phase, greater concentration of soluble protein could enhance foam formulation (Eltayeb et al, 2011). The increase in foaming properties observed at alkaline pH of walnut protein isolate and concentrate (Mao & Hua, 2012) and kariya protein hydrolysates Adiamo, Gbadamosi, and Abiose (2016b) in the report of, agrees to the assertion that foaming properties are pH dependent. The two new varieties of Bambara groundnut samples (BGB and BGW) showed superior foaming capacities over the commercial sample.…”
Section: Effect Of Ph and Nacl Concentration On Emulsifying Activitsupporting
confidence: 83%
“…Adiamo et al . () through the enzymatic hydrolysis of kariya seed protein isolate by pancreatin and pepsin were also reported that high content of hydrophobic amino acids are responsible for the strong reducing power of peptides.…”
Section: Resultsmentioning
confidence: 95%
“…; Adiamo et al . ). It is known that this property is closely related to conditions of hydrolysis as well as enzyme types (Elavarasan et al .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations